Hygiene guideline for the planning, installation, and operation of ventilation and air-conditioning systems in health-care settings - Guideline of the German Society for Hospital Hygiene (DGKH) - Külpmann, Rüdiger; Christiansen, Bärbel; Kramer, Axel; Lüderitz, Peter; Pitten, Frank-Albert; Wille, Frank; Zastrow, Klaus-Dieter; Lemm, Friederike; Sommer, Regina; Halabi, Milo (German Medical Science GMS Publishing House, 2016)
Since the publication of the first "Hospital Hygiene Guideline for the implementation and operation of air conditioning systems (HVAC systems) in hospitals" () in 2002, it was necessary due to the increase in knowledge, new regulations, improved air-conditioning systems and advanced test methods to revise the guideline. Based on the description of the basic features of ventilation concepts, its hygienic test and the usage-based requirements for ventilation, the DGKH section "Ventilation and air conditioning technology" attempts to provide answers for the major air quality issues in the planning, design and the hygienically safe operation of HVAC systems in rooms of health care.